LEARNING STYLES AND TACHING METHODS IN ENGLISH TEACHING - Loly Novita (INOVISH JOURNAL, 2019)
A teacher has resposibilities in building the students’ character, morality and intellectual capability. What he does for the students will give great effect for the future of a nation. A teacher needs to do self-continuous improvementin teaching because he is the one who is responsible to transfer knowledge and value. In performing his teaching task, he needs to understand his students’ personality to ease him find out the precise methods, strategies, approaches and models of teaching applied during teaching and learning process takes time. Understanding the students’ personality in learning will lead the teacher to be successful in teaching because he knows what to do with different students who have different ability. It is a must for a teacher to make someone who knows nothing become the one who knows many things and know how to solve any problem.The teacher will also do his best to apply various methods of teaching in order that he can attract the students’ attention to learn more about the subject. Knowing the students personality, such as their energy, brain hemisphere, modality, and multiple intelligences will really be helpful for the success of teaching.